EXOSOMES AND DEVELOPMENT OF TUMOR CELL RESISTANT PHENOTYPE - M. A. Krasilnikov; A. M. Scherbakov; S. E. Semina (Сибирский онкологический журнал)
Exosomes are 30–100 nm-sized microvesicles that are generated in the cells and released into the extracellular space. Exosomes carry the various bioactive molecules including different types of RNA (miR, lncRNA, mRNA), DNA, proteins, lipids etc. The main exosomes property is the ability to incorporate into the recipient cells resulting in the cascade of both genomic changes (caused by the integration of exosomal DNA) and nongenomic changes (caused by the modulation of the expression or content of the proteins, microRNA etc.). In this review, we discuss the modern conception concerned with the structure and mechanism of the action of tumor exosomes and their role in the tumor progression and formation of tumor-like phenotype in the cells. Specially, the role of the exosomes in the tumor resistance including drug resistance, irradiation resistance and hormone independency was considered. Finally, the diagnostic potential of exosome analysis and its perspectives in the clinical practice were discussed.